In vivo targeting of B-cell lymphoma with glycan ligands of CD22 - Chen, Weihsu C. (American Society of Hematology, 2010)
Antibody-mediated cell depletion therapy has proven to provide significant clinical benefit in treatment of lymphomas and leukemias, driving the development of improved therapies with novel mechanisms of cell killing. A current clinical target for B-cell lymphoma is CD22, a B-cell–specific member of the sialic acid binding Ig-like lectin (siglec) family that recognizes α2-6–linked sialylated glycans as ligands. Here, we describe a novel approach for targeting B lymphoma cells with doxorubicin-loaded liposomal nanoparticles displaying high-affinity glycan ligands of CD22. The targeted liposomes are actively bound and endocytosed by CD22 on B cells, and significantly extend life in a xenograft model of human B-cell lymphoma. Moreover, they bind and kill malignant B cells from peripheral blood samples obtained from patients with hairy cell leukemia, marginal zone lymphoma, and chronic lymphocytic leukemia. The results demonstrate the potential for using a carbohydrate recognition–based approach for efficiently targeting B cells in vivo that can offer improved treatment options for patients with B-cell malignancies.